A Government Ill Executed: The Depletion of the Federal Service. - Light, Paul C. (Public Administration Review, 2008)
The federal government’s “quiet crisis” of the 1980s has become the “deafening crisis” of the early twenty-first century. Virtually every measure of the state of the public service as envisioned by Alexander Hamilton has worsened over the past two decades. This lecture outlines Hamilton’s seven characteristics of an energetic federal service and examines recent trends in its decline. Although the federal service still executes an enormous agenda of important missions, it is increasingly frustrated in its work.